THE ROLE OF PESANTREN IN PRESERVING THE TRADITION OF PEGON ARABIC WRITING: A STUDY IN THE PESANTREN ILMU Al-QURAN SINGOSARI - Rosyidatul Hikmawati; Nafik Muthohirin (El-Jaudah : Jurnal Pendidikan Bahasa dan Sastra Arab, 2024)
Abstract: Pesantren as a traditional Islamic educational institution still has a vital role in preserving the literacy tradition, especially in writing Pegon Arabic. Arab Pegon is the result of the acculturation of Arab intangible culture with Javanese culture through a writing system. Following the customs of the Muslim community in Java, where Arab culture is present, Pegon Arabic writing is written in various languages such as Javanese, Sundanese, Madura, and other regional languages in Indonesia. This reality gave birth to a literacy tradition that continues to grow. However, not many pesantren use Pegon Arabic script writing in Indonesian. The tradition of Pegon Arabic literacy in Islamic boarding schools in Java generally uses the local language, but the practice of writing Pegon Arabic script in the Singosari Islamic Boarding School uses Indonesian. The purpose of this study is to determine the role of Pesantren Ilmu Al-Qur’an Singosari in the preservation of the tradition of Arabic Pegon writing in Indonesian. This study uses qualitative research methods which include the collection of documentation, interviews, and observations. The findings of the study show that the Pesantren Ilmu Al-Qur’an Singosari is accustomed to the practice of Pegon Arabic writing in almost all religious literacy activities. This habit has been proven to be able to increase students’ interest and understanding of Pegon Arabic writing. This article concludes that pesantren play a strategic role in preserving the heritage of the Pegon Arabic writing tradition. In addition, it is important to teach Pegon Arabic writing literacy in Indonesian to students to attract their interest in studying Islamic books by classical scholars. Keywords: Pesantren, Arabic Pegon, Ulama, Islam, Cultural Preservation